The mediating role of leader-member exchange in the relationship between paternalistic leadership and turnover intention: A study on millennial employees in China - Zong Lu Song; Tze Cheng Chew; Borhan Sareya Abdullah (Macrothink Institute, 2024)
This study investigates the relationship between three-dimensional paternalistic leadership and turnover intentions among millennial employees in China, with a focus on the mediating role of leader-member exchange (LMX). A sample of 241 millennial employees from private enterprises was analyzed using SPSS and PLS techniques. The findings indicate that LMX effectively mediates the influence of three-dimensional paternalistic leadership on turnover intentions. The study's use of single respondent and cross-sectional data may limit the robustness and generalizability of its conclusions. Nevertheless, the results offer valuable insights for management practices and decision-making processes in organizations. This research contributes to the literature by highlighting LMX as a crucial mediator in the relationship between three-dimensional paternalistic leadership and turnover intentions among millennial employees. It underscores the importance of further exploring LMX's mediating role in similar contexts, thereby advancing theoretical understanding and practical applications in leadership and employee retention strategies.